Options for suitable biofuel farming: Experience from Southern Africa - Graham von Maltitz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Southern African countries' interest in biofuel is due of its rural development potential. Finding models to optimize this benefit is therefore paramount. High-energy-density crops with low perishability allow farmers to grow small quantities on existing lands. Highly perishable, low-density crops such as sugarcane require tight integration between growers and mills. Models where growers have full ownership in the feedstock production facilities are possible, but this normally means that smallholder farmers need to work as a unit to achieve benefits of scale. Finding market-based mechanisms to ensure sound and equitable returns for land and labour inputs is critical.
Keywords: Q11; Q13; Q42; 330; biofuel; jatropha; sugarcane; rural development; ethanol; Southern Africa